Insecticide resistance and species diversity in Anopheles gambiae s.l. in Côte d’Ivoire - Rosine Z. Wolie; Alphonsine A. Koffi; Joseph Chabi; Ludovic P. Ahoua Alou; Eleanore D. Sternberg; Kouakou P. M. Kouame; Florent H. A. Yapo; Soromane Camara; Amal Dahounto; Innocent Z. Tia; Welbeck A. Oumbouke; Kallista Chan; et al. (PLoS ONE, 2025)
Background Insecticide resistance in malaria vectors poses a significant threat to effective control of malaria vectors across sub-Saharan Africa. In Côte d’Ivoire, Anopheles gambiae s.l. exhibits considerable variability in species distribution and insecticide resistance levels across distinct ecological areas. This study reports on insecticide resistance profiles within An. gambiae complex as well as species composition dynamics in various ecological settings in Côte d’Ivoire. Methods From July to October 2020, larval and adult mosquitoes were collected across three ecological settings (savannah, pre-forest and forest) in Côte d’Ivoire. Larvae were reared to adult stage for susceptibility bioassays. Diagnostic concentrations (DCs) applied against An. gambiae s.l. were deltamethrin 0.05%, permethrin 0.75% and pirimiphos methyl 0.25% using WHO susceptibility test kits. When increased survival to diagnostic concentrations (DCs) was observed, intensity bioassays were conducted using 5x and 10x DCs. In addition, synergist assays were performed at the DC level with pre-exposure to 4% piperonyl butoxide (PBO). Together with adults directly collected from the field, female samples from the bioassays outcome were speciated and resistance target site mechanisms (Kdr L1014F and Ace-1R G119S) were determined using PCR. Species distribution and insecticide resistance were analyzed across ecological areas. Results Significant variations in insecticide resistance phenotypes and mechanisms in An. gambiae s.l. were found across the three ecological areas in Côte d’Ivoire. Mortality rates, following pyrethroid exposure, were significantly higher in An. gambiae s.l. collected in the savannah zone compared to those collected from the forest zone (p < 0.05). An. gambiae was more predominant in the savannah area (98.8%, 95% confidence of interval (CI) [93.5–100.0]), whereas An. coluzzii dominated in the pre-forest (92.9%, 95% CI [88.9–95.8]) and forest zones (61.3%, 95% CI [53.4–68.9]). Such predominance of An. coluzzii was associated with high intensity of pyrethroid resistance in these areas. Overall, the allelic frequencies of the resistance mutations in An. gambiae were higher than those in An. coluzzii regardless of the area. Kdr L1014F frequency in the forest zone was 78.1% (95% CI [68.0–88.2]) in An. gambiae larvae, 51.8% (95% CI [33.3–70.4]) in adults, and 63.1% (95% CI [52.4–73.8]) in An. coluzzii larvae. Conclusion Variations in species distribution and insecticide resistance in ecological areas in Côte d’Ivoire should be carefully considered when developing and implementing vector control strategies.